Are Students of Secondary Schools of Seven Districts Different on Their Self-Estimates of Multiple Intelligences? A Case Study of Southern Districts of Khyber Pakhtunkhwa - Shahzada, Gulap; Khan, Habib Nawaz; Muhammad Khan, Ayaz; Ullah, Hakim (Frontiers in Education, 2021)
Self-assessment of intelligence is a personal belief of ability, which is counted for an important portion of success in life. With 905 students of secondary schools of seven districts of Khyber Pakhtunkhwa, a survey study was conducted in order to find out students’ self-estimates and the differences of self-estimates on multiple intelligences. Data were collected from the subjects through a valid and reliable inventory. For a selection of the sample, a stratified, random, and proportion allocation technique was used; tests of between-subject effects, analysis of variance, and post hoc were applied as an inferential statistical test. The result of the study revealed that students of Lakki Marwat estimated their logical/mathematical, intrapersonal, verbal/linguistic, and visual/spatial intelligence to be higher than those of the students in the other districts. Students of Bannu rated their musical intelligences higher than that of the students of other districts. Students of Hango estimated their bodily/kinesthetic intelligence higher than that of the students of other districts. Students of Kohat estimated their existential intelligence higher than that of the students of other districts. Researchers suggested that schools should give such an environment of learning to the students where all the intelligences can be focused and promoted.